COLIFORM SPECIES DIVERSITY IDENTIFICATION IN RTE DAIRY PRODUCTS - N. B. Shadrova; O. V. Pruntova; G. S. Skitovich (Ветеринария сегодня)
The paper presents the results of testing of RTE dairy products submitted to the FGBI “ARRIAH” Testing Centre in 2016 for Coliform identification. The species diversity of isolated bacteria was identified, properties of common Coliforms were characterized and possible sources of contamination were analyzed. Escherichia, Enterobacter, Citrobacter, Raoultella, Klebsiella, Cronobacter were identified. The detection rate of E. coli was 61.3%, which suggests post pasteurization contamination of dairy products from production environment.